Pengaruh Sertifikasi Halal dan Kepuasan Pelanggan terhadap Loyalitas Konsumen pada Daifuku Mochi Sangatta Utara (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study aims to analyze the extent to which halal certification and customer satisfaction affect consumer loyalty at Daifuku Mochi in Sangatta Utara. The approach used is quantitative with field research methods. Data were obtained through questionnaires, direct observation at the store, and documentation. The study population amounted to 1000 people, and the sample was determined as many as 50 respondents using the quota sampling technique. The analysis was carried out with multiple linear regression which resulted in the equation Y = 2,394 + 0.360X1 + 0.541X2, indicating a positive influence between the two independent variables on consumer loyalty. The t-test results show that customer satisfaction has a significant effect on loyalty (tcount 3.166 > ttable 2.011; sig. 0.003 < 0.05), while halal certification is not partially significant (tcount 1.443 < ttable 2.011; sig. 0.156 > 0.05). However, simultaneously, both have a significant effect on consumer loyalty (Fcount 6.171 > Ftable 3.19; sig. 0.004 <0.05). The R² value of 0.375 indicates that 37.5% of the variation in customer loyalty can be explained by the two variables, while the rest is influenced by other factors outside this study.